Current trends of minimally invasive therapy for cholecystocholedocholithiasis - Cominardi, Anna; Aragona, Giovanni; Cattaneo, Gaetano; Arzù, Gian; Capelli, Patrizio; Banchini, Filippo (Frontiers in Medicine, 2023)
Introduction:The minimally invasive approach by endoscopic ultrasound(EUS)-guided procedures for cholecystocholedocholithiasis, such as EUS-guided gallbladder drainage(EUS-GBD),percutaneous gallbladder drainage(PT-GBD),EUS-guided rendezvous(EUS-RV) and EUS-guided biliary drainage(EUS-BD), is affirming as a good treatment for patients with acute cholecystitis(AC) unfit for surgery and for patients with common bile duct stones (CBDSs) with a previous ERCP failure. Moreover, in case of difficult CBDSs extraction during ERCP, the cholangioscopy-guided electrohydraulic lithotripsy (CS-EHL) showed optimal results. The primary aim of our study was to evaluate the efficacy of EUS-GBD and PT-GBD in patients with AC unfit for surgery, the efficacy of EUS-GBD, EUS-BD and EUS-RV after ERCP failure and the efficacy of CS-EHL for difficult CBDSs extraction in our hospital. The secondary aim was to evaluate the safety of these procedures. Materials and methods:We retrospectively evaluated all the EUS-GBD, PT-GBD, EUS-BD, EUS-RV and CS-EHL prospectively collected in the Gastroenterology and General Surgery Units from January 2020 to June 2023. The efficacy was expressed as technical and clinical success; the safety as adverse events (AEs) rate. Results:We collected 83 patients with AC and high-surgical risk. Among them, 57 (68.7%,) patients underwent EUS-GBD and 26 (31.3%) underwent PT-GBD. Technical and clinical success were 96.5% and 100% for EUS-GBD and 96.1 % and 92% for PT-GBD. AEs for EUS-GBD were 1.7% and for PT-GBD 12%.ERCP for CBDSs extraction failed in 77 patients. In 73/77 (94.8%) was performed EUS-RV with a technical and clinical success of 72.6% and 100%. No AEs were reported. 4/77 patients were directly treated with EUS-BD for pyloric inflammatory stenosis. In 12 (16.4%) patients after unsuccessful EUS-RV with CBD diameter ≥ 12 mm, a EUS-BD was performed. EUS-BD technical and clinical success were both of 100% and no AE was reported. EUS-GBD was the treatment of choice for the remaining 8 (10.9%) patients after ERCP and EUS-RV failure. The procedure had high technical and clinical success (both 100%) and no AEs.Also the 12 difficult CBDSs extraction treated with CS-EHL, showed high technical and clinical success (both 100%) without reporting AEs. Conclusion:The minimally invasive approach for cholecystocholedocholithiasis, especially EUS-guided procedures, had a high efficacy and safety.